Quality of life in patients with melasma in Turkish women - Hacer Uyanikoglu; Mustafa Aksoy (PAGEPress Publications, 2017)
The aim of this study was to determine the impact of melasma on quality of life (QoL) using the dermatology life quality index (DLQI) questionnaire in a group of outpatients. This study is questionnairebased. A total of 101 Turkish women suffering from melasma, who themselves were able to understand and complete the Turkish version of the DLQI questionnaire, were enrolled. This questionnaire included 10 questions; each of each was scored on a scale of 0-3, with a maximum score of 30. The data were analyzed after the results had been collated and the higher the DLQI score, the poorer the QoL. The participants' mean age was 29.53±6.87 years, and mean DLQI score was 6.02±4.94. When we divided the participants into two subgroups according to age, the DLQI scores for younger and older individuals were 7.44±4.99 and 4.33±4.36, respectively (P=0.001). When the melasma area and severity index (MASI) score was used, participants with mild and moderate disease had mean DLQI scores of 5.80±4.72 and 7.11±5.90, respectively. No patient had severe disease. Melasma might affect the participants' QoL, especially that of the younger individuals, in our study population.